(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2026)
Religious culture has long been recognized as an influential social phenomenon shaping moral values, collective identity, and patterns of social interaction. In contemporary societies characterized by globalization, cultural pluralism, and social transformation, maintaining social cohesion has become an increasingly complex challenge. This article explores the role of religious culture in strengthening social cohesion by examining its moral, cultural, and social functions. Employing a qualitative methodology based on document analysis and comparative literature review, the study analyzes scholarly perspectives on religion as a cultural system contributing to social solidarity, tolerance, and communal integration. The findings demonstrate that religious culture continues to function as a significant source of shared values, ethical norms, and social trust. The article argues that, when interpreted inclusively and integrated within broader cultural frameworks, religious culture can positively contribute to social cohesion without contradicting secular principles. The study concludes by highlighting the need for further empirical research into the interaction between religious culture and social cohesion in diverse societal contexts.